2005
DOI: 10.1177/230949900501300305
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Vertebral Osteomyelitis: A Review of 14 Cases

Abstract: combination of the 2. The mean period of antibiotic use was 11.4 weeks. One patient with melioidosis involving the T9 to T11 vertebrae caused by P pseudomallei died of empyema and septicaemia 22 months after presentation. Conclusion. Pyogenic vertebral osteomyelitis is not uncommon in the elderly, especially those with predisposing conditions such as diabetes mellitus. Computed tomography-guided needle biopsy is recommended to investigate causative microorganisms. Aggressive surgical debridement and prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…After a surgical debridement and subsequent 4 weeks of intravenous antibiotic therapy, the patients underwent autogenous bone grafting and anterior plating. Since then, several series have been presented with patients undergoing anterior corpectomy and plate fixation [10,15,24,30,37,38,44,48,51], but the number of patients enrolled in these studies was relatively small and most of them were cervical cases.…”
Section: Discussionmentioning
confidence: 99%
“…After a surgical debridement and subsequent 4 weeks of intravenous antibiotic therapy, the patients underwent autogenous bone grafting and anterior plating. Since then, several series have been presented with patients undergoing anterior corpectomy and plate fixation [10,15,24,30,37,38,44,48,51], but the number of patients enrolled in these studies was relatively small and most of them were cervical cases.…”
Section: Discussionmentioning
confidence: 99%
“…The advocates for spinal instrumentation argued that stabilization of the spine is very important for the suppression and eventual elimination of infections [13,14]. Increasing evidence has also showed that instrumentation in the presence of active infection is well tolerated while spinal stability is maintained effectively with sufficient restoration of sagittal alignment of the spine and relatively shorter duration of bed rest [3,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively reported that the most common causative pathogen is Staphylococcus aureus (S. aureus), followed in frequency by Streptococcus species, Escherichia coli, Staphylococcus epidermis, Aeruginosus Bacillus and Pseudomonas [7,8,17,19,31,35,36,47,52,56,64,71]. A large scale study singled out S. aureus as the most common infective agent with a frequency as high as 48% (123/255).…”
Section: Microbiologymentioning
confidence: 99%
“…1) [17,21,22,25,28,32,36,42,44,49,55,56,65,66,71]. The majority of operations were performed in a fashion of combined approach, which account 66% in 312 procedures.…”
Section: Anterior or Posterior Approachmentioning
confidence: 99%
See 1 more Smart Citation